Liver-FDG-uptake augments early PET/CT prognostic value for CD19-targeted CAR-T cell therapy in diffuse large B cell lymphoma - Beck, Michael; Blumenberg, Viktoria; Bücklein, Veit L.; Bundschuh, Ralph A.; Harrer, Dennis C.; Hirschbühl, Klaus; Jung, Johannes; Kunz, Wolfgang G.; Menhart, Karin; Winkelmann, Michael; Yakushev, Igor; Illert, Anna Lena; et al. (EJNMMI Research, 2025)
Background: Despite revolutionary efficacy of CD19-CAR-T cell therapy (CAR-T) in aggressive B cell lymphoma, many patients still relapse mostly early. In early failure, distinct drugs support CAR-T which makes reliable and early prediction of imminent relapse/refractoriness critical. A complete metabolic remission (CR) on Fluor-18-Deoxyglucose (FDG) Positron-Emission-Computed Tomography (PET) 30 days after CAR-T (PET30) strongly predicts progression-free survival (PFS), but still fails in a relevant proportion of patients. We aimed to identify additional routine parameters in PET evaluation to enhance CAR-T response prediction. Results: Thirty patients with aggressive B cell lymphoma treated with CAR-T were retrospectively analyzed. Pre-CAR-T, LDH was the strongest PFS-predictor also by multivariate analysis. Post-CAR-T, 10 out of 14 patients (71.4%) with PET30-CR remained in disease remission, while 12 out of 16 patients (75%) with incomplete metabolic remission (PET30-nCR) relapsed after CAR-T. 28.6% of patients with PET30-CR ultimately progressed. Change of liver FDG-uptake from baseline to day30 (Delta-Liver-SUVmean) was identified as an independent biomarker for response. PET30-nCR and a decrease of Delta-Liver-SUVmean were associated with a high risk of tumor progression (HR 4.79 and 3.99, respectively). The combination of PET30 and Delta-Liver-SUVmean identified patients at very low, at intermediate and at very high risk of relapse (PFS not reached, 7.5 months, 1.5 months, respectively). Conclusion: Additionally to PET30 metabolic remission, longitudinal metabolic changes in Delta-Liver-SUVmean predicted CAR-T efficiency. Our results may guide early intervention studies aiming to enhance CAR-T particularly in the very high-risk patients.
CRIS-Team Scopus Importer:2025-04-01
Keywords: CAR T cell therapy; DLBCL; FDG PET; Liver-SUV